The Application Of Science In Contextual Learning To Improve Students' Science Literacy - Andi Putra; M Giatman; Dedy Irfan; Hansi Efendi (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study aims to analyse the effectiveness of science applications in contextual learning in improving students' science literacy. This study uses a quantitative approach with a single group pretest and posttest design on eighth grade students of junior high schools in urban areas. Data were collected through science literacy tests based on literacy competency indicators, learning implementation observation sheets, and documentation. Data analysis techniques were performed using descriptive analysis, calculation of learning outcome improvement, and mean difference tests. The results showed that the application of science-based contextual learning was able to significantly optimise students' science literacy, especially in the competencies of explaining scientific phenomena, designing and evaluating scientific investigations, and interpreting scientific data and evidence. Learning that integrates real-life contexts, local knowledge, and problem solving has been proven to make the learning process more meaningful and optimise student engagement. These findings indicate that science application-based contextual learning is effective as a strategy for improving science literacy in science learning.